Deconstructing Twentieth Century Medical Libraries: From Typewriters to Digital Libraries. Issue 3 (2nd July 2016) - Shearer, Barbara
ABSTRACT: The last 40 years has represented a time of change for the profession of library and information science, turning many of our constructs inside out. In 1977 the author attended library school, typewriter in hand, and with no thought that computers would one day alter the experience of "library" for everyone. This reflection provides an opportunity for the author, who was interviewed in this journal in the August 2010 issue (http://www.tandfonline.com/doi/abs/10.1080/15424065.2010.505510 ), to bring closure to a career in gratitude. Included are lessons learned throughout a career that spanned the beginning of the Internet, the arrival of Google, and a resurgence of new medical school libraries. One of the special challenges addressed is successfully juggling the career goals of a two-career marriage.